Numerical Study of Fusion Cross Sections for 12C+12C and 16O+16O Reactions by Using Wong Formula - Yacobus Yulianto; Zaki Zu'ud (Lambung Mangkurat University Press, 2018)
The height of the barrier between the interacting nuclei is one of the interesting topics in nuclear reaction, especially in charged-particle nuclear reactions. Wong formula is one method that can be used to perform such study, especially about fusion cross section. Therefore, a study about fusion cross sections of some light nuclei with Wong formula becomes very interesting to be performed. In this study, the fusion cross sections of 12C+12C and 16O+16O reactions have been calculated by using Wong formula at 12<=E<=32 MeV of energies. The potential of the interacting nuclei was approached by using Woods-Saxon potential. The calculations performed numerically by using both finite different and Nelder-Mead methods. The obtained results of this study have achieved a good agreement with the experimental results and the calculation results of the other researchers. Those results were indicated that Wong formula has good capability in explaining the experimental results concerning fusion cross section of light nuclei.